2012
DOI: 10.1186/1758-5996-4-44
|View full text |Cite
|
Sign up to set email alerts
|

Regional differences in clinical care among patients with type 1 diabetes in Brazil: Brazilian Type 1 Diabetes Study Group

Abstract: BackgroundTo determine the characteristics of clinical care offered to type 1 diabetic patients across the four distinct regions of Brazil, with geographic and contrasting socioeconomic differences. Glycemic control, prevalence of cardiovascular risk factors, screening for chronic complications and the frequency that the recommended treatment goals were met using the American Diabetes Association guidelines were evaluated.MethodsThis was a cross-sectional, multicenter study conducted from December 2008 to Dece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
29
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 25 publications
3
29
0
3
Order By: Relevance
“…Regional disparities in diabetes care have been reported for several countries. Studies from the US and Brazil demonstrated regional differences in the frequency of control exams (e. g., measurements of HbA 1C and blood lipids), or screening for diabetes related complications (e. g., retinopathy and nephropathy) [6,7]. In Switzerland and Norway, regional differences have been observed with regard to HbA 1C , medical treatment and However, there is a lack of studies investigating regional differences of medical care in pediatric patients with type 1 diabetes in Germany.…”
mentioning
confidence: 99%
“…Regional disparities in diabetes care have been reported for several countries. Studies from the US and Brazil demonstrated regional differences in the frequency of control exams (e. g., measurements of HbA 1C and blood lipids), or screening for diabetes related complications (e. g., retinopathy and nephropathy) [6,7]. In Switzerland and Norway, regional differences have been observed with regard to HbA 1C , medical treatment and However, there is a lack of studies investigating regional differences of medical care in pediatric patients with type 1 diabetes in Germany.…”
mentioning
confidence: 99%
“…Recent data show that the prevalence of overweight/obesity in children and adolescents with type 1 diabetes in USA is 31% (11). A similar trend was observed in the Brazilian population according to the Brazilian Type 1 Diabetes Study Group (Brazdiab T1DSG) (12), which is a multicenter study that evaluated the care and the clinical condition of patients with T1D in the whole Brazilian population sponsored by the Brazilian Diabetes Association. Obesity might interfere in the development of chronic micro and macrovascular complications in patients with type 1 diabetes (13,14).…”
mentioning
confidence: 60%
“…T1D treatment has significantly improved in the last decades. Although metabolic control is not ideal in the majority of patients with T1D worldwide (12,25), an evident catabolic state is not generally observed anymore. Therefore, this population is nearly as prone to develop overweight and obesity as the general population, which might influence their risk of hypertension, dyslipidemia, micro and macrovascular chronic complications.…”
mentioning
confidence: 99%
“…In spite of our cross-sectional design, this finding strongly suggests weight excess to be unrelated to intensity of insulin treatment. Moreover, owing to marked social and economic differences observed in our country which have been previously described [23], this sample has a particularly high number of individuals on conventional therapy (i.e., one or two insulin injections per day). This feature is especially suitable to assess the role of intense insulin therapy in this sample.…”
Section: Discussionmentioning
confidence: 99%